A Program for Postgraduate Diploma in Project Planning and Management - Kabale University (Kabale University, 2022)
The programme aims at providing participants with knowledge and skills necessary for effective performance in the role of project manager. It adopts a generic approach to project management and is designed for projects in construction and engineering, events management, research and development, community services, trade, tourism and agricultural projects. The programme consists of 13 compulsory taught courses while the second part will involve a project inform of an extended essay.